Semi-analytical Study on the Flow of Magnetohydrodynamic Nanofluid with Slip Effects - Sivasankari, S.; Ananthaswamy, V. (Discontinuity, Nonlinearity, and Complexity, 2026)
The current study addresses the slip Magnetohydrodynamic upper-convective Maxwell Casson nanofluid flow through an extended porous surface, including chemical reactions and thermal radiation. The Modified Homotopy analysis methodology is utilized to resolve the governing reduced equations. The semi-analytical responses for the velocity, concentration and temperature in dimensionless forms are attained and given in explicit form. The efficiency and convergence of the approach are then depicted by comparing the acquired findings with a numerical result. The effects of a number of physical parameters included in the model are illustrated graphically. The semi-analytical expressions of physical quantities in dimensionless form, including the Sherwood number, Nusselt number and skin friction factor are calculated and interlined graphically. To show how the physical quantities affect the results, tables are given. With this strategy, the error approximation yields relatively small values. Moreover, the slip factors of velocity and concentration have a positive impact on the temperature, while the slip factors of velocity have a negative impact on concentration and velocity.